2012
DOI: 10.1017/s0007114512002978
|View full text |Cite
|
Sign up to set email alerts
|

Casein glycomacropeptide in the diet may reduceEscherichia coliattachment to the intestinal mucosa and increase the intestinal lactobacilli of early weaned piglets after an enterotoxigenicE. coliK88 challenge

Abstract: Casein glycomacropeptide (CGMP), a glycoprotein originating during cheese manufacture, has shown promising effects by promoting the growth of some beneficial bacteria in vitro, although its activity has not been well explored. The present study was designed to evaluate the effects of CGMP against enterotoxigenic Escherichia coli (ETEC) K88 in vitro (Trial 1) and in vivo (Trial 2). In Trial 1, increasing concentrations of CGMP (0, 0·5, 1·5 or 2·5 mg/ml) were tested regarding its ability to block the attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…Our results are consistent with the study of Chen et al [14], who used a small amount of GMP (0.1 mg/day), where the amount of Lactobacillus and Bifidobacterium was significantly increased in the fecal samples of mice. In addition, piglets receiving a diet supplemented with GMP over 15 days show increased lactobacilli numbers in the ileum and proximal colon [29], and mice chronically fed a GMP-enriched diet have a significant increase in Bacteroides in their feces compared to those fed a casein-enriched diet [30]. In a series of prospective studies analyzing differences in the composition of the intestinal flora between allergic and nonallergic infants, colonization with Bifidobacterium and Bacteroides during the first years of life appeared to be associated with protection against allergy [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the study of Chen et al [14], who used a small amount of GMP (0.1 mg/day), where the amount of Lactobacillus and Bifidobacterium was significantly increased in the fecal samples of mice. In addition, piglets receiving a diet supplemented with GMP over 15 days show increased lactobacilli numbers in the ileum and proximal colon [29], and mice chronically fed a GMP-enriched diet have a significant increase in Bacteroides in their feces compared to those fed a casein-enriched diet [30]. In a series of prospective studies analyzing differences in the composition of the intestinal flora between allergic and nonallergic infants, colonization with Bifidobacterium and Bacteroides during the first years of life appeared to be associated with protection against allergy [11,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, K88 challenged piglets supplied with 1% CGMP showed a similar growth performance and fecal scores as control group, which suggested the ability of CGMP to alleviate the negative effect caused by K88 challenge. However, Hermes et al. (2013) reported that neither CGMP diet nor enterotoxigenic E. coli (ETEC) challenge had impact on growth performance or feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the result of intestinal E. coli counts, it is interesting to remark that the amount of significant enterobacteria E. coli both in cecum and colon contents of CGMP treated group was not increased after K88 challenge. Several researches reported that less adhesion of K88 on intestinal mucosa or Caco-2 cells after CGMP treated ( Bruck et al., 2006 , Gonzalez-Ortiz et al., 2014 , Hermes et al., 2013 ). Hermes et al.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA was eluted in 200 mL of Qiagen buffer AE and stored at −80°C until use. A SYBR green qPCR targeting the gene coding the F4 fimbria of E. coli K88 was performed according to the procedure described by Hermes et al (2013). Results are expressed as cfu/g of fresh matter (FM) and log of F4 gene copies/g FM.…”
Section: Methodsmentioning
confidence: 99%